2010
DOI: 10.1021/bc1003982
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Protein Cross-Linking by Peroxidase-Catalyzed Activation of a Tyrosine-Containing Peptide Tag

Abstract: Protein modification methods represent fundamental techniques that are applicable in many fields. In this study, a site-specific protein cross-linking based on the oxidative tyrosine coupling reaction was demonstrated. In the presence of horseradish peroxidase (HRP) and H(2)O(2), tyrosine residues undergo one-electron oxidation reactions and form radicals in their phenolic moieties, and these species subsequently react with each other to form dimers or further react to generate polymers. Here, a peptide-tag co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 48 publications
2
80
0
Order By: Relevance
“…For example, proteins presenting tyrosine moieties at their surface can be gelled in the presence of laccases or peroxidases/H 2 O 2 ( Figure 20) [147][148][149][150]. Next to proteins also natural polymers exhibiting phenolic side chains can be gelled enzymatically.…”
Section: Polymer Modificationmentioning
confidence: 99%
“…For example, proteins presenting tyrosine moieties at their surface can be gelled in the presence of laccases or peroxidases/H 2 O 2 ( Figure 20) [147][148][149][150]. Next to proteins also natural polymers exhibiting phenolic side chains can be gelled enzymatically.…”
Section: Polymer Modificationmentioning
confidence: 99%
“…The EGFP(Y237F) was used because in our previous report, it was shown that the wild-type EGFP cross-linked by itself upon HRP treatment probably due to the tyrosine residue at its penultimate C-terminal position. 22 SA mutants, model proteins, and HRP were mixed together in 10 mM Tris-HCl (pH 8.0) at final concentrations of 0.2 mg/ mL, 0.2 mg/mL, and 0.1 mg/mL, respectively. The heteroconjugation reaction was conducted by adding H 2 O 2 in the same manner as described above, and the sample solutions were analyzed by SDS-PAGE.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
“…The differences in the resulting bands were caused by the following reason ( Figure 4). The BAP-GY cross-links by itself through its GY-tag mostly in a linear form, 22 which appears as mBAP dimers in SDS-PAGE analysis (lane 2 for BAP-GY in Figure 1A and Figure 4A). Meanwhile, the positively charged Y-tags are capable of cross-linking with the intrinsic tyrosine residues of BAP, resulting in mBAP polymers (lane 2 for BAP-RY and BAP-RYR in Figure 1A and as depicted in Figure 4B).…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations